2006
DOI: 10.1095/biolreprod.105.048165
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Insulin-Like Peptide 3 (INSL3) Hormone-Receptor (LGR8) System in the Testis1

Abstract: The new peptide hormone insulin-like peptide 3 (INSL3) is a member of the insulin-relaxin family, yet, unlike insulin, it signals through a new G-protein coupled receptor, LGR8, distantly related to the receptors for LH and FSH. INSL3 is produced in large amounts by the Leydig cells of the testis in both fetal and adult mammals. Using a combination of mRNA analysis by RT-PCR, immunohistochemistry, ligand-binding, and/or bioactivity assays, the distribution of LGR8 expression was assessed in testicular tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
79
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 50 publications
9
79
1
Order By: Relevance
“…Importantly, cotransfection experiments with wild-type and mutant receptor did not show any effect on the function of the wild-type receptor, suggesting a true loss-of-function nature of the mutation (9). It is interesting to note that the recent estimates indicate that only a very limited number of endogenous LGR8 receptor molecules are expressed in adult Leydig cells (2) and in embryonic gubernaculum (S. Feng and A. I. Agoulnik, unpublished data). Significantly, the presence of only one-half of the functional receptors in heterozygotes appears to be detrimental for INSL3 signaling in humans, contrary to the situation in mice, where the null allele of Lgr8 is fully recessive.…”
Section: Discussionmentioning
confidence: 95%
“…Importantly, cotransfection experiments with wild-type and mutant receptor did not show any effect on the function of the wild-type receptor, suggesting a true loss-of-function nature of the mutation (9). It is interesting to note that the recent estimates indicate that only a very limited number of endogenous LGR8 receptor molecules are expressed in adult Leydig cells (2) and in embryonic gubernaculum (S. Feng and A. I. Agoulnik, unpublished data). Significantly, the presence of only one-half of the functional receptors in heterozygotes appears to be detrimental for INSL3 signaling in humans, contrary to the situation in mice, where the null allele of Lgr8 is fully recessive.…”
Section: Discussionmentioning
confidence: 95%
“…This is based on the findings that the BTB separates mitotic spermatogonia from meiotic germ cells and is periodically disassembled to allow the passage of preleptotene spermatocytes across the barrier (Lui & Lee 2009, Mruk & Cheng 2010, Cheng & Mruk 2012. Although no studies to date have identified the possible sites of action of INSL3 in the boar testis, RXFP2 mRNA and/or protein have been shown to be expressed in Leydig cells, germ cells, and/or Sertoli cells in different species, including humans (Anand- Ivell et al 2006a), rats (Kawamura et al 2004, Anand-Ivell et al 2006a), mice (Anand-Ivell et al 2006a, Feng et al 2007, roe deer (Hombach-Klonisch et al 2004), and goats . In this study, however, we clearly showed that RXFP2 transcripts were expressed mainly in seminiferous germ cells with a weak signal in Sertoli cells, but not in Leydig cells, although the specific germ cell types that expressed the RXFP2 protein could not be identified because of the absence of reliable anti-RXFP2 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The development of a specific immunoassay system using a synthetic peptide consisting of an A-B heterodimer based on human and rodent cDNA sequences has revealed that circulating INSL3 levels increase progressively during pubertal development (Boockfor et al 2001, Ferlin et al 2006, Wikström et al 2006, Anand-Ivell et al 2009) with a subsequent decline by aging in males (Anand-Ivell et al 2006b). In addition, the receptor RXFP2 in INSL3 has been detected in seminiferous germ cells (Kawamura et al 2004, Anand-Ivell et al 2006a, Feng et al 2007) and Leydig cells (Anand-Ivell et al 2006a, Feng et al 2007). Furthermore, INSL3 was reported to suppress male germ cell apoptosis in the testes (Kawamura et al 2004) and to stimulate the proliferation of the mouse Leydig cell line TM-3 (Feng et al 2007), whereas another study reported no effect of INSL3 on either adult-type rat and mouse primary Leydig cells or the mouse Leydig cell tumor cell line MA-10 (Ivell & Anand-Ivell 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The antiserum used in this study was generated against recombinant MBP-RXFP1 endodomain, and its specificity was validated by demonstrating the recognition of RXFP1 endodomain, but not RXFP2 endodomain, on western blotting, and by indicating the immunolocalisation in uterine endometrium and myometrium where RLN receptor is expressed in humans, rodents and pigs (Mercado-Simmen et al 1982, Weiss & BryantGreenwood 1982, Kohsaka et al 1998, Bond et al 2004. The expression of RLF/INSL3 receptor RXFP2 is also observed in the testis of humans (Anand- Ivell et al 2006) and rodents (Feng et al 2007), but it is clear that our generated antiserum does not detect the RXFP2 since it did not cross react with recombinant RXFP2 as mentioned above. To our knowledge, there have been no previous attempts to identify RLN receptor RXFP1 in the boar testis, although there is presently only one study reporting that the testis has specific RLN binding.…”
Section: Discussionmentioning
confidence: 99%